Grundtvigs væksttanke - Fra menneskelivets begyndelse til dets fuldendelse - Fibiger, Lise Brandt (Grundtvig-studier, 1977)
Grundtvigs View of the Growth of Man: From the Beginning of Human Life to its Perfectionby Lise Brandt Fibiger Grundtvig never discusses growth in the sense of bodily growth only or Christian growth only. On the contrary, he always speak of the growth of natural man and of the growth of natural and recreated man, in the sense that natural man is the person who has within him a living faith in God as the Creator, and who enjoys a childlike trust in God. Man is not natural unless he acknowledges his creation. Natural man grows in body and soul, and the natural human life is the absolute prior condition for re-creation to occur. Re-creation takes place in baptism, where man receives Jesus as his brother, and the child’s condition in his relationship with God. The natural man does not lose his significance, for the baptized man is natural and re-created, and growth now occurs according to the same order of things. By insisting that the natural and the re-created human life are a unity Grundtvig avoids a «oiritualization of the Christian life. Growth takes place here and now, in and thiough natural human life. When the child is baptized and has assumed the child’s conditions and Jesus as his brother, God’s Word and Spirit can take root in his heart. As the creative word and spirit God’s Word and Spirit have been in the heart before baptism - now this creative word and spirit are united with the redeeming Word and Spirit. So it is not a new Word and a new Spirit that has entered into existence, but rather a development of them. From the Word and the Spirit in the heart grow faith, hope and love. This traid also belonged to the natural human life; this triad is also developed; and it is with this triad that man grows. But growth does not come of its own accord. Just as man in the natural life must have nourishment in order to grow, so must the natural and re-created man be nourished, and thus whoever is baptized must come to Holy Communion and there get the nourishment to continue his growth. Nourishment is necessary because only through the church service does growth continue unhampered. In life there are still obstacles; man loses faith in his creation and re-creation. If growth is not to stop completely, whoever is baptized must join in the service, where he is able to grow again and where he is nourished and strengthened. Growth cannot be spiritualized, for it is not a Sundays-only growth but an everyday growth. It is not a growth away from the world but a growth in the world in which God’s Kingdom is reflected.